Requisitos de manutenibilidade no projeto: o caso de duas instituições federais de ensino - Costa, Vitória Silveira da; Canteiro, Marcelo Batista; Ferreira, Rodrigo Heling; Schramm, Fábio Kellermann (SIMPÓSIO BRASILEIRO DE GESTÃO E ECONOMIA DA CONSTRUÇÃO, 2021)
Maintainability is related to the ease, accuracy, safety, and economy of maintenance tasks within that system. Since Operation, Maintenance, and Repair Costs are greater than three times the cost of initial construction, a good design can directly contribute reduce these costs in the building's lifecycle. Maintainability has not been widely considered during the design stage because there is a lack of knowledge about the building maintenance as well as about design detailing. This paper discusses the integration of building maintenance requirements into design stage in two Brazilian Federal Educational Institutions. A survey was carried out, divided into two phases. Firstly, design and maintenance departments members of both Institutions was interviewed, in order to identify the integration degree of maintenance requirements in design activities. Secondly, participants were invited to answer a questionnaire, to evaluate the awareness and importance of inserting maintenance requirements into design. The results highlight the importance of the integration between the department teams, to improve design collaboration. Also, stimulating the adoption of feedback mechanisms can be essential to improve both the design and the maintenance process, to reduce maintenance costs and improve building performance.